Vitimizando para proteger: uma análise das propostas de políticas para adolescentes apresentadas na Câmara dos Deputados - Gregorut, Adriana Silva (2019)
The objective of this research is to study draft legislation regarding teenagers proposed before the Federal Congress during the last 12 years. Taking from the theoretical framework of political economy of punishment to reflect on the disputes around agenda, categories, concepts, problems and solutions in the legislative branch, regarding youth in Brazil. Firstly, we developed a quantitative study on all draft legislation proposed during the above- mentioned period that takes teenagers as the main audience, dividing this legislation between categories, through an inductive methodology (using Grounded Theory). Subsequently, we proposed a more extensive qualitative study on the approved bills during the research period, with an aim at identifying the problems raised by the proposed legislation, the solutions put forward and the representation of youth found in documents made available in the Federal Congress database. The objective was to develop a critical analysis over the categories regarding social problems involving the youth, taking neoliberalism and its influence on social reality as a broader context.